BTB domain mutations perturbing KCTD15 oligomerisation cause a distinctive frontonasal dysplasia syndrome - Miller, K; Cruz Walma, D; Pinkas, D; Tooze, R; Bufton, J; Richardson, W; Manning, C; Hunt, A; Cros, J; McGowan, S; Twigg, S; Chalk, R; et al. (BMJ Publishing Group, 2024)
Introduction: KCTD15 encodes an oligomeric BTB domain protein reported to inhibit neural crest formation through repression of Wnt/beta-catenin signalling, as well as transactivation by TFAP2. Heterozygous missense variants in the closely-related paralogue KCTD1 cause scalp-ear-nipple (SEN) syndrome.